2022
DOI: 10.1002/cctc.202201229
|View full text |Cite
|
Sign up to set email alerts
|

Tailored Particle Catalysts for Multistep One‐pot Chemoenzymatic Cascade in Pickering Emulsions

Abstract: Chemoenzymatic cascades are an important tool for advanced synthesis in chemistry. However, these cascades are often limited due to the incompatibility issue between two distinct catalysts and reactions. To address this issue, we present a simple multistep one-pot platform, in which nanoparticle catalysts are prepared to allow chemo-and biocatalytic reactions performed sequentially in water and Pickering emulsions. The preparation of particle catalysts is accomplished in just two steps by polymer modifications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 56 publications
(43 reference statements)
0
0
0
Order By: Relevance
“…The use of particle-assisted emulsions, also referred to as Pickering emulsions, is an alternative to the use of molecular surfactants to confine the catalytic species. Recently, Wu et al 387 reported the Pickering chemo-enzymatic cascade for the one-pot synthesis of chiral esters from ketones (Scheme 103). The authors prepared a silica nanoparticle catalyst containing anchored chiral Ru( ii ) complexes that act not only as heterogeneous metal catalysts to reduce the ketone into the alcohol, but also as active emulsifiers that form Pickering emulsions to encapsulate the lipase CALB, which catalyzes the subsequent enantioselective esterification of the alcohol.…”
Section: Reaction Engineering Strategies For Solving Incompatibility ...mentioning
confidence: 99%
“…The use of particle-assisted emulsions, also referred to as Pickering emulsions, is an alternative to the use of molecular surfactants to confine the catalytic species. Recently, Wu et al 387 reported the Pickering chemo-enzymatic cascade for the one-pot synthesis of chiral esters from ketones (Scheme 103). The authors prepared a silica nanoparticle catalyst containing anchored chiral Ru( ii ) complexes that act not only as heterogeneous metal catalysts to reduce the ketone into the alcohol, but also as active emulsifiers that form Pickering emulsions to encapsulate the lipase CALB, which catalyzes the subsequent enantioselective esterification of the alcohol.…”
Section: Reaction Engineering Strategies For Solving Incompatibility ...mentioning
confidence: 99%